2019
DOI: 10.1371/journal.pntd.0007473
|View full text |Cite
|
Sign up to set email alerts
|

N-linked glycosylation of the West Nile virus envelope protein is not a requisite for avian virulence or vector competence

Abstract: The N-linked glycosylation motif at amino acid position 154–156 of the envelope (E) protein of West Nile virus (WNV) is linked to enhanced murine neuroinvasiveness, avian pathogenicity and vector competence. Naturally occurring isolates with altered E protein glycosylation patterns have been observed in WNV isolates; however, the specific effects of these polymorphisms on avian host pathogenesis and vector competence have not been investigated before. In the present study, amino acid polymorphisms, NYT, NYP, N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 46 publications
(84 reference statements)
0
13
0
Order By: Relevance
“…1C) (14)(15)(16)(17)(18). For instance, most WNV strains (such as NY99) are glycosylated at N154, but some strains, such as Kunjin, are not (19,20). Similarly, all Asian lineage ZIKV strains, such as H/PF/2013 and PRVABC59, are glycosylated at N154, whereas some of the African lineage ZIKV strains are not (21)(22)(23).…”
Section: Flavivirus Envelope Protein Glycosylationmentioning
confidence: 99%
See 1 more Smart Citation
“…1C) (14)(15)(16)(17)(18). For instance, most WNV strains (such as NY99) are glycosylated at N154, but some strains, such as Kunjin, are not (19,20). Similarly, all Asian lineage ZIKV strains, such as H/PF/2013 and PRVABC59, are glycosylated at N154, whereas some of the African lineage ZIKV strains are not (21)(22)(23).…”
Section: Flavivirus Envelope Protein Glycosylationmentioning
confidence: 99%
“…These observations highlight that it can be challenging to define whether the glycan per se mediates infection, as opposed to the specific amino acid residues that comprise the glycosylation signal. For example, different amino acid substitutions at E154/156 of WNV conferred distinct avian host and vector competence phenotypes independent of E-protein glycosylation status (20). Likewise, a ZIKV mutant lacking E glycosylation via a T156I mutation, was unable to bind to DC-SIGNR-expressing cells, whereas a N154Q mutant retained some binding activity (26).…”
Section: Envelope Protein Glycosylation and Attachmentmentioning
confidence: 99%
“…For example, the four DENV serotypes all contain an N-linked glycosylation site at N153, while TBEV contains one at position N154 ( Goto et al, 2005 ; Yoshii et al, 2013 ). Other studies have even shown DI glycosylation to differ between various strains of the same virus, with most WNV strains (such as NY99) displaying glycosylation at N154, but other strains such as Kunjin virus (KUNV) containing none ( Alsaleh et al, 2016 ; Maharaj et al, 2019 ). Similarly, some African lineage ZIKV contain no glycosylation sites while all Asian lineage ZIKV strains are glycosylated at N154 ( Carbaugh et al, 2019 ; Ladner et al, 2016 ).…”
Section: Flavivirus Structural Proteins: Structure and Functionmentioning
confidence: 99%
“…The differences in glycan location and number has also been postulated to be a defining factor in the pathogenic or tropic nature of specific flaviviruses ( Sirohi et al, 2016 ). For example, the glycosylation at N154 in WNV was found to be a requirement for neuroinvasiveness ( Alsaleh et al, 2016 ; Maharaj et al, 2019 ). More research into the structural, and by extension pathological, differences in flavivirus glycosylation is required to understand their significance more fully.…”
Section: Flavivirus Maturation and Egressmentioning
confidence: 99%
“…The crystal structure of the E protein reveals three distinct domains: a β-barrel-shaped domain I, an elongated finger-like domain II, and a C-terminal immunoglobulin-like domain III 8 . Domain I, in the center of the E protein, has a glycosylated amino acid at position 154, which is important for WNV infection of vertebrates 9 . The internal fusion peptide loop at the tip of domain II promotes the trimerisation of the E protein for the initiation of viral entry 8 .…”
mentioning
confidence: 99%